PENERAPAN MODEL SINEKTIK PADA PEMBELAJARAN ARANSEMEN MUSIK COMBO DI SLB N - A PAJAJARAN BANDUNG - Nugraha, Lutfi (2014)
Abstract: This thesis entitled "The application of the sinektik model on arrangement musical combo studying in slbn -a Padjadjaran Bandung ". One of the important factors that can determine the successful of the learning process is the selection and utilize of appropriate learning by the teacher. During this, the learning model that is applied by the combo subject teachers haven't foster student creativity yet in making arrangements. In this research, researchers tried to apply the sinektik model in combo musical arrangements learning to the first grade students in slbn -a Padjadjaran Bandung. This thesis reports or describes the results of research that has been conducted to see the extent of combo musical arrangements learning using the sinektik. This research is using an evaluative method with qualitative approaching and data collection techniques that obtained through a learning process in the front of the class, interviews with the students and combo subject teachers. Based on the qualitative data the research results of the 5 students as the research subjects were followed for 4 meetings the learning process of data analysis results show that by using sinektik models, students are able to make their own arrangements to a song that has been determined.